Exploring Students' Perception on Sustainable University: Empirical Findings in IPB University, Indonesia - Utami, Anisa Dwi; Qayim, Ibnul; Putra, Heriansyah; Mardiana, Rina; Dwiyanti, Fifi Gus; Khoirunisa, Hana; Khairunnisa, Zayyaan Nabiila (Journal of Sustainability Perspectives, 2025)
Universities play a key role in driving positive change by equipping students to address environmental and social challenges. This study examines how students at IPB University perceive various sustainability initiatives implemented on campus. Based on a survey of 1,545 undergraduate students, the research explores their knowledge, awareness, and interest in these efforts. The results show that while most students are familiar with the general concept (87.6%), fewer have knowledge of specific programs, institutional rankings, or the university’s Campus Sustainability Office. Nevertheless, nearly all respondents consider these efforts important (98.7%) and support active student involvement (97.2%). Many also express a desire to see these topics integrated into academic courses (84.9%).These findings highlight the need for improved internal communication and curriculum development to enhance student participation. The study offers both practical and academic insights for improving sustainability strategies in higher education institutions. Future research should include multiple universities and consider mixed-method approaches to better understand the factors influencing student engagement